THE RELATIONSHIP BETWEEN POSITIVE THINKING AND SELF ACCEPTANCE ON ELDERLY IN THE NURSING HOMES: A LITERATURE REVIEW - Retno Indarwati; Neisya Pratiwindya Sudarsiwi; Erna Dwi Wahyuni (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Low elderly self-acceptance in nursing homes affects their quality of life. Elderly difficult to adapting so they feel stressed, lose of control of lives, lose identity. Positive thinking is a form of adaption that can be done by the elderly to have good self acceptance to live in nursong homes. Objective: To know the relationship betwen positive thinking and self-acceptance elderly in nursing homes. Design: A Whittemore and Khanfl’s integrative review was used in this review. Data Sources: This systematic review searched 4 electronic database Scopus, Proquest, Pubmed, Science Direct that published in 2015-2020. Review Methods: Key terms and phrases that utilized were positive thinking OR optimism, self acceptance, elderly OR aged, nursing homes OR orphanage. The JBI Guideline used to asses the quality of each study. Data tabulation and narrative analysis were performed. Results: A total of 11 papers were included in this review. The included studies were divided into three-part, positive thinking in the elderly (n=4), self-acceptance (n=3) and both (n=4). The average number of samples used in each study was 35 people. Conclusion: Positive thinking related to self-acceptance of the elderly in nursing homes. Elders who think positively have a positive mind about themselves, acknowledge and accept various aspects including the good and bad and look at life positively, so they get life satisfaction. The elderly more often feels happiness, enthusiasm to support life, actively appreciate the environment. Good quality of life will increase welfare.